2000
DOI: 10.1074/jbc.275.11.8000
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin Sheds Light on the Singular Case of Seminal RNase, a Dimer with Two Quaternary Conformations

Abstract: Dimeric seminal RNase presents the singular case of a dimer with access at equilibrium to two conformations: one in which the subunits exchange, or swap, their NH 2 -terminal arms; the other with no exchange. Thus a continuous unfolding/refolding of structural elements into two alternative conformations takes place in the native protein at equilibrium. The phenomenon was investigated by kinetic and mass spectrometric analyses of the effects of trypsin on the native protein, on its isolated quaternary forms, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…The replacement of A19P, E28L, K31C, and S32C on RNase A led to domain swapping and to the acquired biological properties (19). It was reported that cross-linked dimer and trimer of RNase A also exhibit these properties (39)(40)(41). It is unknown, however, if the cross-linked dimer is 3D domain-swapped and, if so, if it has the same structure as the unlinked RNase A dimer reported here.…”
Section: Discussionmentioning
confidence: 63%
“…The replacement of A19P, E28L, K31C, and S32C on RNase A led to domain swapping and to the acquired biological properties (19). It was reported that cross-linked dimer and trimer of RNase A also exhibit these properties (39)(40)(41). It is unknown, however, if the cross-linked dimer is 3D domain-swapped and, if so, if it has the same structure as the unlinked RNase A dimer reported here.…”
Section: Discussionmentioning
confidence: 63%
“…From these experiments, we conclude that the nonhyperbolic kinetics observed with the unmodified enzyme are due to the interaction of the substrate with the different subsites of the enzyme rather than to different pre-existing conformations of RNase A (4) or to RNase aggregation (6). This hypothesis is discussed in terms of the configuration of the several binding subsites in RNase A, which is fundamental in relation to the physiological function of the enzyme, i.e.…”
mentioning
confidence: 88%
“…It is well known that RNase A can be split by controlled digestion with subtilisin yielding two fragments, the S-peptide (residues [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and S-protein (residues 21-124), which can be separated easily (28). The separate fragments are inactive.…”
Section: The Substrate Concentration Dependence Of the Reaction Of Rnmentioning
confidence: 99%
“…Consequently, when these experiments are performed using a series of proteases with different specificity under conditions that favors a single bond cleavage (complementary proteolysis), the pattern of preferred cleavage sites will depict the exposed regions in the protein molecule (14,15). This strategy was also employed to investigate conformational changes occurring in protein structure under different experimental conditions (16 -19) or during quaternary forms interchange (20,21), as well as for the definition of the interface regions in protein complexes (22)(23)(24).…”
mentioning
confidence: 99%